Ancient mycobacterial lipids: Key reference biomarkers in charting the evolution of tuberculosis. (June 2015) - Minnikin, David E.; Lee, Oona Y.-C.; Wu, Houdini H.T.; Besra, Gurdyal S.; Bhatt, Apoorva; Nataraj, Vijayashankar; Rothschild, Bruce M.; Spigelman, Mark; Donoghue, Helen D.
Summary: Mycobacterium tuberculosis has a cell envelope incorporating a peptidoglycan-linked arabinogalactan esterified by long-chain mycolic acids. A range of "free" lipids are associated with the "bound" mycolic acids, producing an effective envelope outer membrane. The distribution of these lipids is discontinuous among mycobacteria and such lipids have proven potential for biomarker use in tracing the evolution of tuberculosis. A plausible evolutionary scenario involves progression from an environmental organism, such as Mycobacterium kansasii, through intermediate "smooth" tubercle bacilli, labelled "Mycobacterium canettii" ; cell envelope lipid composition possibly correlates with such a progression. M. kansasii and "M. canettii" have characteristic lipooligosaccharides, associated with motility and biofilms, and glycosyl phenolphthiocerol dimycocerosates ("phenolic glycolipids"). Both these lipid classes are absent in modern M. tuberculosis sensu stricto, though simplified phenolic glycolipids remain in certain current biotypes. Dimycocerosates of the phthiocerol family are restricted to smaller phthiodiolone diesters in M. kansasii . Diacyl and pentaacyl trehaloses are present in "M. canettii" and M. tuberculosis, accompanied in the latter by related sulfated acyl trehaloses. In comparison with environmental mycobacteria, subtle modifications in mycolic acid structures in "M. canettii" and M. tuberculosis are notable. The probability of essential tuberculosis evolution taking place in Pleistocene megafauna, rather than Homo sapiens, is reemphasised.